Juridical Analysis of Massive Traffic Violations Carried Out by the Delivery of the Remains - Zabidin Zabidin (IHSA Institute, 2022)
The bodyguards who carried out massive escorts in carrying out the bodies included violations that often resulted in accidents. Accidents involving motorbikes or cars on the highway that occur due to technical matters, for example, motorbike riders who deliberately hit a car or motorbike who don't want to get out of the way when the motorists delivering the body tell them to move aside, motorists and cars object the road was taken by force and was very undisciplined, as well as the lack of awareness possessed by motorists carrying bodies which resulted in them committing arbitrary acts on the highway. We rarely meet orderly motorists delivering corpses. The factors that cause massive traffic violations committed by funeral drivers are the human factor and the factor of not being escorted by the police. The family of the deceased forced the ushers to speed down the street, indiscipline and ignorance. Meanwhile, preventive efforts are made by guiding the community. attention and guidance are urgently needed as a means to prevent any action that deviates from the values ??that exist in society and prevention efforts against parents or family, the community, the police, and related agencies. if when delivering the body they damage public facilities which can harm themselves or others.